Prevalence and antimicrobial resistance of bacterial meningitis in China from 2017 to 2021: a multicenter retrospective study - Chunyan Zhang; Zheng Li; Mengyuan Wang; Shifu Wang (Journal of Infection in Developing Countries)
Introduction: This study aims to investigate the changing epidemiology and antimicrobial susceptibility of bacteria isolated from cerebrospinal fluid (CSF) in the Shandong region.